One Money, One Cycle? The EMU Experience - Martin Gächter; Aleksandra Riedl (Oesterreichische Nationalbank (OeNB), 2013)
We examine whether the introduction of the euro had a significantly positive impact on the synchronization of business cycles among members of Economic and Monetary Union (EMU) which might arise due to the lack of country-specific monetary policy shocks in the euro area. Empirical evidence on this relationship is rare so far and su ers from methodical weaknesses, such as the absence of time variability, which is crucial for addressing this issue. Using a synchronization index that is constructed on a year-by-year basis (1993-2011), we uncover a strong and robust empirical finding: the adoption of the euro has significantly increased the correlation of member countries' business cycles above and beyond the effect of higher trade integration. Thus, our results substantially strengthen the conclusion by Frankel & Rose (1998), i.e. a country is more likely to satisfy the criteria for entry into a currency union ex post rather than ex ante. Remarkably, however, this reasoning is even verified when controlling for the effect of increased trade linkages implied by entering a currency union.
Keywords: E02; E32; E58; F15; F33; 330; Business cycles; EMU; endogeneity; optimum currency areas; Euro; Konjunkturzusammenhang; Geldpolitik; Optimaler Währungsraum; Eurozone